Adolescent morphine exposure does not alter low-dose lipopolysaccharide (LPS)-induced sickness behavior in adult C57/BL6 mice - Natalie V. Davidson; Cynthia Masese; Caitlin Han; Lili Massac; Yuu Ishikawa; Grace Reynolds; Codey Smithson; Jackson Cook; Melissa T. Manners; Shivon A. Robinson (PLoS ONE, 2025)
Adolescent opioid use in the United States commands attention: millions of twelve- to nineteen-year-olds are exposed to opioids each year by prescription and misuse. Recent findings show that opioids bind not only to canonical opioid receptors but also interact with receptors on immune cells within both the central and peripheral nervous systems. The potential for early life opioid exposure to give rise to long-term changes in the neuroimmune system is not fully understood, particularly given the adolescent brain’s high susceptibility to neuroplastic changes. The goal of this study was to investigate the hypothesis that adolescent opioid use potentiates physiological and behavioral responses to lipopolysaccharide (LPS)-induced sickness later in life. To achieve this, we treated adolescent (postnatal day 35–42) male and female C57/BL6 mice with saline or bi-daily escalating doses of morphine for 5 days to model opioid dependence and, in adulthood (postnatal day 60–67), administered saline or a low dose of LPS (0.1 mg/kg) to promote an immune response. Body weight, body surface temperature, and locomotor activity were recorded up to 48 hours after LPS administration. Mice were also tested in the forced swim test 52 hours after LPS administration to assess depressive-like behavior. In contrast to our hypotheses, we found that adolescent morphine exposure had no additive effect on low-dose LPS-induced sickness measures when assessed in adulthood. These data suggest that adolescent opioid exposure may have minimal effects on future immune challenges, although further research is needed to confirm this.